2018
DOI: 10.1021/acsaem.8b00829
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation with Water on Carbon-Nitride-Based Metal-Free Photocatalysts with 0.1% Solar-to-Ammonia Energy Conversion Efficiency

Abstract: Ammonia (NH 3 ), which is an indispensable chemical, is produced by the Haber−Bosch process using H 2 and N 2 under severe reaction conditions. Although photocatalytic N 2 fixation with water under ambient conditions is ideal, all previously reported catalysts show low efficiency. Here, we report that a metalfree organic semiconductor could provide a new basis for photocatalytic N 2 fixation. We show that phosphorus-doped carbon nitride containing surface nitrogen vacancies (PCN-V), prepared by simple thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 66 publications
4
141
0
Order By: Relevance
“…As mentioned in the previous sections, many studies claimed that the vacancy defects such as oxygen vacancies, nitrogen vacancies, and sulfur vacancies58c–e with their abundant localized electrons can donate their electron for absorbed N 2 , forming chemical bonding between N 2 and surrounded atoms and activating N 2 molecule, therefore, enhancing catalytic performance. The photocatalytic nitrogen fixation performance of NVs assisted P doped carbon nitride have been determined with the high solar conversion efficiency of 0.1% which is comparable with the average efficiency of natural photosynthesis by general plant6a ( Figure a). Moreover, the six‐electron transfer process can also be facilitated in S vacancies supported MoS 2 nanosheets.…”
Section: Advanced Photo(electro)catalysts and Structure Engineeringmentioning
confidence: 64%
See 3 more Smart Citations
“…As mentioned in the previous sections, many studies claimed that the vacancy defects such as oxygen vacancies, nitrogen vacancies, and sulfur vacancies58c–e with their abundant localized electrons can donate their electron for absorbed N 2 , forming chemical bonding between N 2 and surrounded atoms and activating N 2 molecule, therefore, enhancing catalytic performance. The photocatalytic nitrogen fixation performance of NVs assisted P doped carbon nitride have been determined with the high solar conversion efficiency of 0.1% which is comparable with the average efficiency of natural photosynthesis by general plant6a ( Figure a). Moreover, the six‐electron transfer process can also be facilitated in S vacancies supported MoS 2 nanosheets.…”
Section: Advanced Photo(electro)catalysts and Structure Engineeringmentioning
confidence: 64%
“…For photocatalytic reaction, a high specific surface area photocatalyst performs the better activity as compared to the similar photocatalyst with low surface area, particularly for H 2 evolution, and CO 2 conversion . However, it seems that the photocatalytic performance of nitrogen fixation has less dependence on this factor . Hirakawa and coworkers compared the activities of commercial TiO 2 catalysts with different surface areas .…”
Section: Fundamental Challenges Of Photo(electro)catalytic Nitrogen Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the above discussions, developing effective strategies to achieve high‐efficiency g‐C 3 N 4 ‐based photocatalyst, capable of improving the N 2 adsorption/activation and visible‐light utilization, simultaneously effectively inhibiting the recombination of photogenerated carriers in g‐C 3 N 4 , is critically important and highly needed. Recently, Shiraishi and co‐workers have demonstrated that heteroatom doping could be an effective means to regulate the electronic structures of g‐C 3 N 4 , thus obtaining new catalytic active sites (N vacancy) for N 2 adsorption and activation, leading to an high‐efficiency NH 3 synthesis performance 17. More importantly, Wang et al theoretically predicted that B‐doping in g‐C 3 N 4 can not only improve the visible‐light utilization efficiency, also reaching rather low onset potential for photocatalytic NRR based on the concept of electron “acceptance–donation” on B atoms, similar to that of transition metals 5,18.…”
Section: Introductionmentioning
confidence: 99%